Moral Intelligence of Students in Padang 7 High School - Risna Wati Tampubolon; Yusri Yusri (Universitas Negeri Padang, 2019)
Moral intelligence is the ability to understand things that are right and wrong means, have strong ethical beliefs and act on these beliefs, so that people behave properly and respectfully. This study is praised to measure: (1) students' moral intelligence on aspects of empathy, (2) moral intelligence of students in aspects of conscience, (3) moral intelligence of students in aspects of self-control, (4) moral intelligence of students in aspects of respect, (5) moral intelligence of students in aspects of kindness, (6) moral intelligence of students in aspects of tolerance , (7) moral intelligence of students in aspects of justice. This research uses a quantitative approach with descriptive methods. The sample in this study were grade X, XI, XII students of SMA Negeri 7 Padang, totaling 292 students. the data collection tool used was a questionnaire. Data analysis techniques used descriptive statistical analysis.The results showed that: (1) the moral intelligence of students in SMA 7 Padang based on aspects of empathy was in the high category with a percentage of 54,11%. (2) moral intelligence of students in SMA N 7 Padang based on conscience is in the high enough category with a percentage of 58.56%. (3) the moral intelligence of students in SMA N 7 Padang based on aspects of self-control is in the high enough category with a percentage of 66.10%. (4) the moral intelligence of students in SMA N 7 Padang based on the respect aspect is in the quite high category with the percentage 55.14%. (5) moral intelligence of students in SMA N 7 Padang based on the aspect of tolerance is in the quite high category with a percentage of 51.37%. (6) the moral intelligence of students in SMA N 7 Padang based on aspects of kindness is in the high enough category 45.21% (7) the moral intelligence of students in SMA N 7 Padang based on aspects of justice is in the quite high category with a percentage of 61,99%.Based on the research findings it is suggested to the counselor teacher to be able to support and continue to monitor the moral development of students so that good morale can be maintained and the BK teacher seeks to improve the moral intelligence of students through the provision of BK services in schools relating to student morals.